Fysiske faktorers betydning for mattilbudet i barnehagene – en casestudie - Aadland, Eli Kristin; Holthe, Asle; Wergedahl, Hege; Fossgard, Eldbjørg (Nordisk barnehageforskning, 2014)
Abstract: The purpose of this article is to put focus on food and meal situation in the kindergarten. We have carried out a case study in two kindergartens and the data material consists of observations and interviews. The results showed that the physical structures such as the food and drink offer, structural facilities and the physical community are important for the food and meal provision in the kindergarten. The provision of food and drink varied between the two cases, this can be explained by how the kindergartens organized the preparation of the meal. Emphasis of the dining environment was different in the two cases, which in turn created a different atmosphere around the meal. It was also different practices whether the staff ate together with the children or not. When the staff ate the same food as the children, the meals were in a greater extent characterized by the adults’ needs, including increased demands on hygiene, more delicate garnished food, greater food selection and the increased focus on the dining environment. The distance to the nearest grocery store had little impact, while on the other hand, cooperation with food suppliers had great importance for food and meal provision in the kindergarten. Sammendrag: Case studien har sett på fysiske faktorer som kan hemme eller fremme muligheter for helsefremmende handling i barnehagen. Resultatene viste at mattilbudet i barnehagen var påvirket av hva som tilbys av mat/drikke, bygningsmessige fasiliteter og det fysiske nærmiljøet. Barnehagene hadde ulik praksis med å spise med barna. Når voksne spiser samme maten som barna, ser det ut som måltidene blir formet etter voksnes behov. Som økt krav til hygiene, at maten er delikat servert, større matvareutvalg og økt krav til trivelig spisemiljø. Nærhet til butikk hadde liten betydning, mens derimot samarbeid med grossister for levering av matvarer, hadde stor betydning for mattilbudet i barnehagen.